1027 Differences in Polysomnography-Based Sleep Disorders Between HIV-Infected Persons and Matched Controls. (27th May 2020) - Chen, Y; Chen, C; Strollo, P J; Li, C; Ko, W; Lin, C; Ko, N
Abstract: Introduction: Sleep disturbance is a prevalent problem among HIV-infected persons. The recognition of comorbid sleep disorders in patients with HIV is currently hampered by limited knowledge of sleep-related symptoms, sleep architecture, and types of sleep disorders. We aimed to compare the differences in sleep-related symptoms and polysomnography-based sleep disorders between HIV-infected persons and controls. Methods: The study included 170 men with a Pittsburgh sleep quality index (PSQI) greater than 5, composed of 44 HIV-infected men and 126 male controls who were frequency-matched by sex, age (-/+ 3.0 years) and BMI (-/+ 3.0 kg/m2). For all participants an overnight sleep study using a Somte V1 monitor was conducted. Differences in sleep-related symptoms and sleep disorders between HIV-infected patients and controls were examined using t-tests or Chi-square tests. Results: HIV-infected persons with sleep disturbances more often had psychological disturbances (72.7% vs. 40.5%, p<0.001) and suspected rapid eye movement (REM) behavior disorder (RBD) (25.0% vs. 4.8%, p<0.01) than that of controls. The sleep-disordered breathing (SDB) in HIV-infected persons was less common than that in controls (56.8% vs. 87.3%, p<0.001). The mean percentage of REM sleep among HIV-infected patients was higher than that among the controls (20.6% vs. 16.6%, p<0.001). Enuresis was more common in HIV-infected persons than controls (40.9% vs. 22.2%, p=0.02). Conclusion: Psychological disturbances and SDB can be the possible explanations of sleep disturbances in HIV-infected persons, in which suspected RBD is notable. Further studies are warranted to examine underlying factors of suspected RBD among HIV-infected persons with sleep disturbances. Support: This work was supported by the Ministry of Science and Technology, Executive Yuan of Taiwan [MOST 105-3011-E-006-002], and National Cheng Kung University Hospital [NCKUH-10702022]